Bentuk-Bentuk Topeng Bali Sebagai Sumber Inspirasi Penciptaan Seni Lukis - Jayadwiana, I Made; Karja, I Wayan; Mudana, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
The writing of the MBKM Independent Study report takes ideas or ideas about Forms of Balinese masks as Inspiration for the Creation of Painting Artwork, from phenomena that the author encounters in mask performances during barong and keris dance performances and during piodolan ceremonies at Pura Dalem Segara, as well as at Pura Batubulan village center, observation of mask and tapel craftsmen at Br. Puaya and Jeleka Batuan Sukawati and the tapel collection that the author personally owns. The author has a view on masks Balinese traditional masks, that beautiful object shapes can make masks a source of inspiration in this Independent Study work, therefore the author chose Wiradana art studio as a place to study as well as a second studio to deepen skills and broaden imagination. Of course, with the guidance of Mr. Made Wiradana, he directs the writer in his work and forms the character of the tips in the works that will be made to answer what is the goal of this work, the creation method is by exploring, improvising, and shaping. By composing art elements, and going through the stages of exploration, improvisation, and the formation stage, as well as combining them with ideas and ideas so as to create 6 works entitled: 1) “jatayu and Barong ket”, 2) “Rangda”, 3) “Naga Basuki” , 4)